Subclinical hypothyroidism: to treat or not to treat, that is the question! A systematic review with meta-analysis on lipid profile. Issue 3 (April 2017) - Abreu, Isabel M; Lau, Eva; de Sousa Pinto, Bernardo; Carvalho, Davide
Abstract : Previous studies suggested that subclinical hypothyroidism has a detrimental effect on cardiovascular risk factors, and that its effective treatment may have a beneficial impact on overall health. The main purpose of this review and meta-analysis was to assess whether subclinical hypothyroidism treatment is of clinical relevance, based on cardiovascular risk parameters correction. A systemic research of the literature using MEDLINE tool was performed to identify the relevant studies. Only placebo-controlled randomized control trials were included. A quantitative analysis was also performed. This systematic review and meta-analysis of randomized placebo-controlled trials assess the different impact of levothyroxine vs placebo treatment. A significant decrease in serum thyroid-stimulating hormone and total and low-density lipoprotein cholesterol was obtained with levothyroxine therapy (66, 9 and 14%, respectively) and, although modest, this could be significant in terms of reduction of the incidence of coronary artery disease. Other significant results of lipid parameters were not obtained. This systematic review provides a strong evidence-based data in favour of specific changes and beneficial effects of levothyroxine treatment.